Development and optimization of zingerone-loaded PLGA oil-based nanocarriers for enhanced solubility and sustained drug release - Varsha Laxman Jakune; Varsha Siddheswar Tegeli (Journal of Applied Pharmaceutical Research, 2026)
Background: Zingerone, a phenolic constituent of Zingiber officinale, possesses notable antioxidant, anti-inflammatory, and anticancer activities. Its therapeutic use is limited by poor water solubility and low oral bioavailability, resulting in suboptimal efficacy. Polymeric nanocarriers, especially poly(lactic-co-glycolic acid) (PLGA)-based systems, offer an effective approach to enhance solubility, stability, and controlled drug delivery. Integration of lipid components into PLGA matrices can further improve drug loading and solubilization. This study focused on the design and optimization of zingerone-loaded PLGA oil-based nanocarriers to improve solubility and sustained release. Methodology: Solubility screening of zingerone in different oils identified peanut oil as the most suitable vehicle (54.31 mg/ml). Nanocarriers were prepared using a solvent evaporation method, producing nine formulations (F1–F9) with varying oil content and homogenization speeds. Characterization included particle size and zeta potential analysis, FTIR, DSC, SEM, and drug content determination using UV spectroscopy and HPLC. Drug release was studied using a dialysis membrane in phosphate buffer (pH 6.4), and stability testing was performed for the optimized formulation. Results and Discussion: The optimized batch (F4) exhibited a particle size of 79.7 nm, a zeta potential of −27.3 mV, and a drug content of 99.73%. Solubility increased more than 30-fold (5.44 mg/ml), with sustained drug release reaching 97.7% over 24 hours. Characterization confirmed efficient encapsulation and formulation stability. Conclusion: PLGA oil-based nanocarriers significantly improved zingerone solubility and enabled controlled release, indicating strong potential for further pharmacokinetic and therapeutic evaluation.